A 3D‐Bioprinted Vascularized Glioblastoma‐on‐a‐Chip for Studying the Impact of Simulated Microgravity as a Novel Pre‐Clinical Approach in Brain Tumor Therapy (Adv. Therap. 11/2021). Issue 11 (18th November 2021) - Silvani, Giulia; Basirun, Carin; Wu, Hanjie; Mehner, Christine; Poole, Kate; Bradbury, Peta; Chou, Joshua
Abstract : This cover image represents the bioconvergence between microfluidics, 3D bioprinting, lab‐on‐chip and microgravity technologies to develop a new approach towards the development and understanding of complex biological microenvironments including brain cancer which is described in this study. The emergence of space mechanobiology has demonstrated potential to unveiling biological mechanisms and disease function. This is reported by Joshua Chou and co‐workers in article number 2100106 .